Soil pollution from monitoring to remediation - Duarte, Armando C.; Cachada, Anabela; Rocha-Santos, Teresa (Academic Press, 2018)
Soil Pollution: From Monitoring to Remediation provides comprehensive information on soil pollution, including causes, distribution, transport, the transformation and fate of pollutants in soil, and metabolite accumulation. The book covers organic, inorganic and nanoparticle pollutants and methodologies for their monitoring. Features a critical discussion on ecotoxicological and human effects of soil pollution, and strategies for soil protection and remediation. Meticulously organized, this is an ideal resource for students, researchers and professionals, providing up-to-date foundational content for those already familiar with the field. Chapters are highly accessible, offering an authoritative introduction for non-specialists and undergraduate students alike.--Provided by publisher.